Knowledge-based collaborative decision making in product design - Qiu, Yuanfu (2008)
This research aims to understand how knowledge is used in various design activities from a human factors perspective, and develop a methodology that can be used to support collaborative decision making in product design. Based on the literature review, surveys and interviews, important factors for the support of collaborative decision making in product design were identified. A knowledge-based collaborative decision making model was developed. Knowledge in product design was identified and the knowledge processing was described. A knowledge modeling method was developed for knowledge-based collaborative decision making support. Experimental studies were undertaken to explore the understanding of knowledge, activities and design space. The results provide the understanding of the content, action and context of knowledge in product design. The results also provide the answers to what knowledge is used, how the knowledge is communicated, and how the knowledge is integrated into design space in different design phases. The theoretical implications for future research and practical implications were presented. This research may improve the integration of human and knowledge-based systems. It will provide rich insight for research in knowledge management, team collaboration and decision making in product design.